ECONOMIC COMPETITIVENESS OF SHEEP EXPORTS OF SUDAN IN SAUDI ARABIA (Journal of Veterinary Medicine and Animal Production, 2022)
Sudan has a wealth of livestock composed of cattle, sheep goats and camels. Livestock production in Sudan occurs mainly under the traditional rain fed sector, which depends on the natural pastures of Kordofan, Darfur, White Nile, Blue Nile and Gezira and other regions as well. This traditional sector is the main source of supply of livestock (live animal or red meat) for the domestic and foreign markets. Sheep exports constitute the main livestock earning foreign currency in Sudan. The purposes of this study is to estimate the competitiveness of sheep exports to Saudi Arabia using three sizes of sheep (small, medium and large) to come up with useful policy for improving sheep exports of Sudan. The study used the policy analysis matrix (PAM) method to estimate the extent of market prices distortion and the degree of misallocation of resources. Primary data and secondary data were collected from relevant sources including the Ministry of Animal Resources, Pastures and Fisheries, Ministry of Foreign Trade, traders and exporters’ representatives of sheep in Khartoum State. The results of the study indicated the competitiveness and the positive financial and economic profits of the three sizes of exported sheep. The total cost of exporting one head of sheep increases as the size of the sheep increases. Similarly, the private and economic profits increase as the size of the exported sheep increase. The study recommended revision of the taxing and fees levy policies and to reduce the gap between the nominal and the real (economic) exchange rate to remove implicit taxes imputed in the exports of sheep from Sudan to Kingdom of Saudi Arabia
Keywords: livestock; PAM; sheep